O kompetencji (prawnej) stron i metodzie dokonywania czynności procesowych w sądowym postępowaniu cywilnym - Błaszczak, Łukasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
This article concerns the powers to act in court proceedings, with particular emphasis placed on the attributes of the parties to the proceedings. The powers to act in court proceedings are analyzed in the context of the capacity to act in court proceedings, and the power to take actions of legal significance. The term ‘powers’ is employed here in a similar context to that used in the theory of law. In addition,the paper analyzes the issue of whether civil proceedings should draw their terminology from the theory of law.
Keywords: czynność procesowa; kompetencja; norma prawna; zdolność procesowa; zdolność postulacyjna; zdolność sądowa; wadliwość